Micro CT Analysis of Geopolymer Composites - Bakalova, Totka; Kolínová, Marcela; Louda, Petr (Manufacturing Technology Journal, 2014)
There are many situations when you need information about the internal structure of the materials. Computed Tomography (CT) is a non-destructive method of evaluating the internal structure, which was originally used for medical examination of the human body. Today it is already used in many different fields, where the aim is the examination of the internal structure of the material. Geopolymer is a term for all inorganic polymeric materials which are prepared from alumino-silicate materials by geopolymerization in alkaline environment at normal temperature and pressure. Computed tomography (CT) is an advanced method that allows the study of the structure based geopolymer composites with short fibers or nanoparticulate reinforcement.
Keywords: computerized tomography (CT); non-destructive method; internal structure; geopolymer